(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The experiment was conducted on the private farm in Al-mussiabMasshroaa regions during Summer seasons 2016 to study the effect of foliar application by 4 concentration of potassium (0, 100,200,300) mgk.L-1 and 4 concentration of calcium (0,50,100,200) mgCa .L-1 and interaction on growth and yield of green gram . Randomized complete block design (RCBD) with three replications was used .The results showed that the level 200 mg K.L-1 giving the highest average height plant , plant dry weight ,pods number ,seed number and seeds yield for plantwhile dominance the concentration 100mg K.L-1 on the seed 1000 weight character, Casprayed had no significant on seed yield